Pengaruh Service Quality dan Patient Safety Expectation Terhadap Customer Satisfaction dan Customer Loyalty Pada AIC Medical Clinic di Masa Pandemi Covid-19 [The Effect of Service Quality and Patient Safety Expectation on Customer Satisfaction and Customer Loyalty on AIC Medical Clinic During the Covid-19 Pandemic] - Kho, Ardi; Budianto, Bernard; Antoni, Irene (Universitas Pelita Harapan, 2022)
This study was conducted during the COVID-19 Pandemic when patients were afraid and avoided going to the clinic so there was a decrease in patient visits to AIC Medical. This study is to find out whether patients prefer patient safety expectations rather than service quality that affects customer satisfaction, and increases customer loyalty. This study was conducted in Jakarta involving 162 patients at AIC Medical Clinic. Data was collected by distributing questionnaires containing 40 statements using a Likert scale of 1–5 based on a non-probability sampling method with a saturation sampling technique. Data were analyzed using the PLS-based SEM method. The research results support some of the proposed models. The findings are service quality, patient safety expectations, and corporate CSR has a positive effect on customer satisfaction. Other research findings that support the relationship between service quality and customer loyalty are positive. The results show that the effect of cultural similarity on customer satisfaction is negative. The findings confirm that customer satisfaction is partial mediation of the relationship between service quality and customer loyalty.BAHASA INDONESIA ABSTRACTPenelitian ini dilakukan pada masa pandemi COVID-19 saat pasien takut dan menghindari untuk ke klinik sehingga terjadi penurunan kunjungan pasien ke AIC Medical Clinic. Penelitian ini untuk mengetahui apakah pasien lebih memilih keamanan atau patient safety expectation daripada service quality yang berpengaruh terhadap customer satisfaction, dan meningkat customer loyalty. Penelitian ini dilakukan di Jakarta dengan melibatkan 162 pasien di AIC Medical Clinic. Pengumpulan data dilakukan dengan menyebarkan kuesioner berisi 40 pernyataan dengan Skala Likert 1–5 berdasarkan metode purposive sampling dengan kriteria pasien yang datang di klinik saat pandemi COVID-19. Data dianalisis dengan metode SEM berbasiskan PLS. Hasil penelitian mendukung sebagian model yang diusulkan, service quality, patient safety expectation dan CSR perusahaan berpengaruh positif terhadap customer satisfaction. Temuan lain penelitian mendukung hubungan service quality terhadap customer loyalty adalah positif. Terdapat pengaruh patient safety expectation terhadap customer satisfaction lebih besar dibandingkan oleh pengaruh service quality, tetapi pengaruh cultural similarity terhadap customer satisfaction adalah negatif. Temuan mengonfirmasi mediasi customer satisfaction mempengaruhi customer loyalty.